The effect of the clinical supervision model on nurses' performance in atrial fibrillation care - Maryam Mokhtari; Asghar Khalifehzadeh-Esfahani; Shahla Mohamadirizi (Wolters Kluwer Medknow Publications, 2022)
Background: A model of clinical education for reducing the theory-practice gap is the clinical supervision model. The purpose of this study was to evaluate the effect of the clinical supervision model on nurses' performance in Atrial Fibrillation (AF) care in a Critical Care Unit (CCU). Materials and Methods: This quasi-experimental study was conducted with a pretest-posttest design. Through stratified random sampling, 36 eligible nurses working in the CCU in Hospitals in Isfahan, Iran, were selected. The data gathering tools included a demographic questionnaire (7 items) and a performance checklist (44 items). Data were analyzed using descriptive (mean and standard deviation) and analytical statistics (ANOVA, LSD, post hoc test, and paired t-test). The level of statistical significance was p ≤ 0.05. Results: Paired t-test showed that there was a significant difference between the mean total scores of nurses' performance and its dimension before and after the intervention (p < 0.001). The results of ANOVA before the intervention showed that there was a significant difference between the mean (SD) scores of care [63.14 (13.08), t = 13.66], pharmacologic [68.98 (13.15), t = 8.20], and electrical cardioversion dimensions [63.37 (10.47), t = 16.82, p < 0.001]. The results of ANOVA showed that the mean (SD) scores of the all dimensions did not differ significantly after the intervention [82.91 (9.75), 84.95 (83.87), and 83.51 (8.07), respectively, p > 0.05]. Conclusions: The clinical supervision model can be used as an educational model combined with supervision to improve nurses' performance in providing care to patients with AF.